Microbiota, mitochondria, and epigenetics in health and disease: converging pathways to solve the puzzle - Rukavina Mikusic, Natalia Lucia; Prince, Paula Denise; Choi, Marcelo Roberto; Chuffa, Luiz Gustavo A. [UNESP]; Simão, Vinícius Augusto [UNESP]; Castro, Claudia; Manucha, Walter; Quesada, Isabel (Springer Nature, 2025)
Dysbiosis, which refers to an imbalance in the composition of the gut microbiome, has been associated with a range of metabolic disorders, including type 2 diabetes, obesity, and metabolic syndrome. Although the exact mechanisms connecting gut dysbiosis to these conditions are not fully understood, various lines of evidence strongly suggest a substantial role for the interaction between the gut microbiome, mitochondria, and epigenetics. Current studies suggest that the gut microbiome has the potential to affect mitochondrial function and biogenesis through the production of metabolites. A well-balanced microbiota plays a pivotal role in supporting normal mitochondrial and cellular functions by providing metabolites that are essential for mitochondrial bioenergetics and signaling pathways. Conversely, in the context of illnesses, an unbalanced microbiota can impact mitochondrial function, leading to increased aerobic glycolysis, reduced oxidative phosphorylation and fatty acid oxidation, alterations in mitochondrial membrane permeability, and heightened resistance to cellular apoptosis. Mitochondrial activity can also influence the composition and function of the gut microbiota. Because of the intricate interplay between nuclear and mitochondrial communication, the nuclear epigenome can regulate mitochondrial function, and conversely, mitochondria can produce metabolic signals that initiate epigenetic changes within the nucleus. Given the epigenetic modifications triggered by metabolic signals from mitochondria in response to stress or damage, targeting an imbalanced microbiota through interventions could offer a promising strategy to alleviate the epigenetic alterations arising from disrupted mitochondrial signaling.
Keywords: Epigenetics; Metabolic syndrome; Microbiota; Mitochondria